Power budget analysis for broadcast passive optical network - Abdullah, Mohammad Faiz Liew (1999)
Optical fibre technology is vital for broadband communication and multimedia applications because single-mode optical fibres have a very low attenuation and a vast bandwidth at 1.3|im and 1.55|im wavelengths regions. The ever increasing demand for high speed data transmission and multimedia applications will inevitably results in optical fibre communication being used to replace copper cables all the way to the subscriber's home. A long term saving in maintenance cost can also be expected. This thesis presents an idealised mathematical model of the power requirement of a simple broadcast Fibre To The Home (FTTH) network based on the bus, star and bus-star topologies. Power requirement at central office (CO) is one of the main parameters that must be taken into consideration by system designers in their planning for the implementation of FTTH. A mathematical model was developed for each of the topology, which relates the power needed at the CO to the parameters of the network such as fibre loss, coupling loss, splitters loss, detection method and signal quality. This software package requires input specifications from the designer, and the output is a complete power budget analysis in a graphical form which can be used to understand the behaviour of each topology related to its power requirement. The numerical results show close agreement with manual power budget calculation using the same set of input parameters. The results can serve as useful guidance for system designers to evaluate the capability at the central office. However, apart from the limited topologies, the software concentrates mainly on one way transmission and limited modulation techniques. Future improvement can be implemented based on the software developed in this thesis.